Educational policy and intergenerational income mobility: Evidence from the Finnish comprehensive school reform - Tuomas Pekkarinen; Sari Pekkala; Roope Uusitalo (Institute for Labour Market Policy Evaluation (IFAU), 2006)
This paper estimates the effect of a major education reform on the intergenerational income mobility in Finland. The Finnish comprehensive school reform of 1972-1977 replaced the old two-track school system with a uniform nine-year comprehensive school and significantly reduced the degree of heterogeneity in the Finnish primary and secondary education. We estimate the effect of this reform on the intergenerational income elasticity using a representative sample of males born during 1960-1966. The identification strategy relies on a difference-in-differences approach and exploits the fact that the reform was implemented gradually across country during a six-year period. The results indicate that the reform reduced the intergenerational income elasticity by about seven percentage points.
Keywords: I20; J62; 330; Intergenerational mobility; education; comprehensive school reform; Bildungsreform; Bildungspolitik; Erwerbsverlauf; Soziale Mobilität; Overlapping Generations; Finnland